THE USE OF ASSETS IN THE PERSPECTIVE OF SHARIA ECONOMIC LAW: (A Study on the Implementation of PBG in Pidie District) - Sabilla, Tacha; Bakri, Nurdi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
This study examines the concept of property use (tasharruf) from the perspective of Islamic economic law through a study of the implementation of the Building Construction Agreement (PBG) in Pidie Regency. The change in the licensing system from Building Construction Permit (IMB) to PBG has significant implications for individual rights in managing building assets. From a sharia perspective, the right of tasharruf is integral to ownership. However, adopting this new regulation faces structural obstacles, namely the lack of ratification of the Qanun PBG at the local level, which creates legal uncertainty and bureaucratic barriers, especially for micro and small businesses. Using a normative-empirical approach that combines classical and contemporary fiqh analysis and field data from interviews, this study finds that using buildings without formal permits cannot be entirely blamed on the community. Instead, the inadequacy of local regulations, lack of socialization, and absence of administrative assistance are the main factors hindering the community. Therefore, this administrative responsibility cannot be entirely attributed to individuals. As a solution, this study recommends the establishment of a responsive PBG regulation, enhanced public awareness campaigns, and providing administrative assistance services to achieve harmony between positive law and Islamic legal principles, thereby ensuring that property rights are exercised fairly and for the common good.